A high-voltage, wide-temperature electrolyte, lithium battery and its application

By using high-voltage and wide temperature domain electrolytes in lithium batteries, using composite solvents and multiple lithium salt electrolytes to form high-entropy local high-concentration electrolytes, the performance problems of lithium batteries at high voltage and wide temperatures are solved, and higher lithium ion mobility and more stable electrode/electrolyte interface are achieved.

CN119447477BActive Publication Date: 2025-03-21TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510032303.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Existing lithium batteries have poor performance at high pressure and a narrow application temperature range, which limits their applicability in high energy density and wide temperature range.

Method used

Using a high-voltage and wide temperature domain electrolyte, including composite solvents and a variety of lithium salt electrolytes, the lithium ion mobility and electrolyte distribution uniformity are improved by forming high-entropy local high-concentration electrolytes.

Benefits of technology

The performance of lithium batteries at ultra-high voltage and ultra-wide temperatures is significantly improved, including excellent Li+ transmission mechanics, thermal stability, electrochemical stability window and flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447477B_ABST
    Figure CN119447477B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery electrolytes, and discloses an electrolyte resistant to high voltage and wide temperature range, a lithium battery and its application. The electrolyte resistant to high voltage and wide temperature range includes a composite solvent and an electrolyte; the electrolyte includes LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB; the composite solvent includes a main solvent with electron donor ability, a diluent for improving the fluidity of the electrolyte, and an additive for improving the solubility of the solute and the ionic conductivity. The electrolyte of the present application uses a composite solvent to form a diversified solvation structure, and uses a variety of lithium salt electrolytes to increase the mixing entropy to enhance the solubility of specific salts, so that a variety of anion groups in the electrolyte interact with lithium ions to form a fluorinated high-entropy local high-concentration electrolyte, which helps to form an inorganic-rich SEI and CEI layer, which has high conductivity, can achieve a more stable electrode / electrolyte interface and a higher lithium ion mobility, and significantly improve the performance of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium battery electrolytes, and in particular to a high-voltage and wide-temperature-range resistant electrolyte, a lithium battery, and applications thereof. Background Art

[0002] Lithium batteries are widely used in electric vehicles, energy storage, consumer electronics and other fields due to their high energy density and long cycle life. In the field of electric vehicles, lithium batteries can significantly increase the driving range and shorten the charging time, thereby improving the user experience; in terms of renewable energy storage, lithium batteries can effectively balance the load of the power grid, store solar and wind energy, and promote the development of sustainable energy. In consumer electronics, the lightweight and high-performance characteristics of lithium batteries also make them an ideal choice for devices such as smartphones and laptops.

[0003] Although lithium batteries have many advantages, they still have some disadvantages that limit their further use. The electrolyte of traditional lithium batteries is prone to decomposition and consumption under high pressure, which destroys the stability of the electrode structure, causing the lithium battery to be intolerant to high pressure, limiting its use in high energy density applications; on the other hand, the electrolyte is prone to oxidative decomposition at high temperatures, resulting in reduced cycle stability of lithium batteries, generating heat, and endangering the safe operation of lithium batteries; based on this, the application temperature range of existing lithium batteries is relatively narrow, and they can usually only work stably under specific environmental conditions, and their performance is reduced in extreme temperature environments.

[0004] The sensitivity of lithium batteries to temperature and voltage not only reduces their reliability, but also limits their applicability in aerospace, military and polar exploration applications that require wide temperature and high voltage operation. Therefore, it is of great significance to develop lithium battery electrolytes and lithium batteries with high voltage resistance and wide temperature range performance. Summary of the invention

[0005] The present application provides an electrolyte, a lithium battery and applications thereof that are resistant to high voltage and a wide temperature range, aiming to solve the problems of poor performance under high voltage and a narrow application temperature range of existing lithium batteries.

[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0007] In a first aspect of the present application, there is provided an electrolyte having high voltage resistance and wide temperature range, comprising a composite solvent and an electrolyte;

[0008] The electrolyte includes LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB;

[0009] The composite solvent includes a main solvent having electron donor capability, a diluent for improving electrolyte fluidity, and an additive for increasing solute solubility and ion conductivity;

[0010] Wherein, the main solvent is 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

[0011] Preferably, the diluent is tris(trifluoromethyl) phosphate; and the additive is fluoroethylene carbonate.

[0012] Preferably, the mass ratio of the main solvent, the diluent and the additive is (1-5):(1-5):1.

[0013] Preferably, in the electrolyte, the total concentration of electrolyte is 3 mol / L, and the concentrations of LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB are the same.

[0014] Preferably, the LiFBr is (3-fluoro-5-bromobenzenesulfonyl) (trifluoromethanesulfonyl) imide lithium, and the preparation method thereof comprises:

[0015] CF3SO2NHK and potassium carbonate are reacted at room temperature in a molar ratio of (1.2-1.5):1, and then 3-fluoro-5-bromobenzenesulfonyl chloride is added dropwise to the reaction solution; after removing the solid phase from the reaction solution, the liquid phase is evaporated to obtain KFBr;

[0016] In acetonitrile solvent, KFBr and LiClO4 are cation exchanged at a molar ratio of (0.2~0.3):1, and then the solid phase is removed and the liquid phase is evaporated to obtain LiFBr.

[0017] Preferably, the preparation method of the 1,1′-oxybis(2-(2-fluoroethoxy)ethane) comprises:

[0018] Deoxyfluorine and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) are added to dichloromethane for reaction, and then sodium bicarbonate solution is added to quench the reaction to obtain a crude product;

[0019] The crude product was extracted with dichloromethane to remove impurities, dried, and then purified by flash chromatography to obtain 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

[0020] Further preferably, the molar ratio of the deoxyfluorine and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) is (2-2.2):1;

[0021] The reaction temperature is 0°C to 25°C; the reaction time is 12h to 15h.

[0022] Preferably, the preparation method of tris(trifluoromethyl) phosphate comprises:

[0023] Under an inert atmosphere, trifluoromethanol and triethylamine are added to xylene and stirred evenly; phosphorus oxychloride is slowly added dropwise at a temperature of 0°C to 3°C to react to obtain a crude product solution;

[0024] The crude product solution is filtered and the filtrate is collected; the filtrate is washed and separated, and the organic phase is collected; the organic phase is dried and concentrated to obtain tris(trifluoromethyl) phosphate;

[0025] Wherein, the molar ratio of trifluoromethanol, triethylamine and phosphorus oxychloride is 1:(0.5-0.6):(1-1.2);

[0026] The concentration is specifically as follows: the organic phase is kept at 35°C-50°C for 1h-2h, and then kept at 50°C-60°C for 1h-2h.

[0027] The second aspect of the present application provides the use of the above-mentioned high-voltage and wide-temperature range electrolyte in a lithium battery.

[0028] In a third aspect of the present application, a lithium battery is provided, comprising a positive electrode, a negative electrode, an electrolyte and a separator; the electrolyte is the above-mentioned high-voltage and wide-temperature-range resistant electrolyte.

[0029] Compared with the prior art, the beneficial effects of this application are:

[0030] The electrolyte of the present application uses a composite solvent to form a diverse solvation structure, and uses a variety of lithium salt electrolytes to increase the mixing entropy to enhance the solubility of specific salts, so that a variety of anion groups in the electrolyte interact with lithium ions to form a fluorinated high-entropy local high-concentration electrolyte. The high disorder weakens the interaction between lithium ions and salts and solvents, making the electrolyte distribution in the electrolyte more uniform. Among them, LiFBr salt can enhance the ion transport selectivity, increase the number of lithium ion migration, and alleviate the concentration polarization phenomenon; 1,1′-oxybis(2-(2-fluoroethoxy)ethane) has excellent electron donor ability and can capture the migrated lithium ions to form a stable five-membered ring structure. The resulting solvated lithium shows a folded molecular geometry, similar to a supramolecular complex, giving the solvated lithium a larger molecular dipole moment and donor number; tris(trifluoromethyl) phosphate as a non-solvated diluent can inhibit the main solvent and additives in the electrolyte from reacting with Li + The affinity of Li + conduction efficiency and improve the fluidity of the electrolyte.

[0031] The fluorinated high-entropy local high-concentration electrolyte of the present application helps to form inorganic-rich SEI and CEI layers, which have high conductivity, can achieve a more stable electrode / electrolyte interface and higher lithium ion mobility, thereby significantly improving the performance of lithium batteries. The lithium battery using the electrolyte of the present application has excellent Li + It has excellent transmission dynamics and thermal stability, a wide electrochemical stability window and excellent flame retardancy, and can work stably under ultra-high voltage (4.7V) and ultra-wide temperature (-50℃~70℃). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 The NMR spectrum of the chemical structure of the main solvent 1,1′-oxybis(2-(2-fluoroethoxy)ethane);

[0034] Figure 2 This is the NMR spectrum of the chemical structure of diluent tris(trifluoromethyl) phosphate;

[0035] Figure 3 Optical morphology of lithium deposition on the copper foil surface at different temperatures for a half-cell assembled with the electrolyte of Example 1;

[0036] Figure 4 Scanning transmission microscope morphology of lithium deposition on the surface of copper foil at different temperatures for a half-cell assembled with the electrolyte of Example 1;

[0037] Figure 5 The electrochemical performance test diagram of the half-cell assembled with the electrolyte of Example 1 at different temperatures;

[0038] Figure 6 Electrochemical performance test diagram of Li||NCM811 full battery assembled with the electrolyte of Example 1 at different temperatures;

[0039] Figure 7 The charge and discharge curves of the 100th cycle of the Li||NCM811 full battery assembled with the electrolyte of Example 1 at different temperatures;

[0040] Figure 8 The electrochemical performance test diagram of the Li||NCM811 full battery assembled with the electrolyte of Example 1 at different current densities and temperatures. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0043] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0045] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0046] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0047] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0048] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] In a first aspect, the present application provides an electrolyte resistant to high voltage and wide temperature range, comprising a composite solvent and an electrolyte;

[0050] The electrolyte includes LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB;

[0051] The composite solvent includes a main solvent having electron donor capability, a diluent for improving electrolyte fluidity, and an additive for increasing solute solubility and ion conductivity.

[0052] In the present application, the main solvent is 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

[0053] In the present application, the diluent is tris(trifluoromethyl) phosphate; the additive is fluoroethylene carbonate. The mass ratio of the main solvent, the diluent and the additive is (1-5):(1-5):1.

[0054] The electrolyte of the present application uses a composite solvent to form a diversified solvation structure, and uses a variety of lithium salt electrolytes to increase the mixing entropy to enhance the solubility of specific salts, so that a variety of anion groups in the electrolyte interact with lithium ions to form a fluorinated high-entropy local high-concentration electrolyte. The high disorder weakens the interaction between lithium ions and salts and solvents, making the electrolyte distribution in the electrolyte more uniform. Among them, LiFBr salt can enhance the selectivity of ion transport, increase the number of lithium ion migration, and alleviate concentration polarization. Due to the enhanced electrochemical reduction and decomposition of the halogenated aromatic anion structure, an SEI interface layer rich in lithium halides (LiF, LiBr, LiCl) is constructed in situ on the surface of the lithium negative electrode. The interface layer has a high Young's modulus and high surface energy to uniformly distribute lithium ions. The SEI layer also has a low lithium ion diffusion barrier, thereby improving the interface stability. 1,1′-oxybis(2-(2-fluoroethoxy)ethane) has excellent electron donor ability and can capture the migrated lithium ions to form a stable five-membered ring structure. The resulting solvated lithium shows a folded molecular geometry similar to a supramolecular complex, and its structure is shown below:

[0055]

[0056] This structure gives the solvated lithium a larger molecular dipole moment and donor number.

[0057] Among them, tris(trifluoromethyl) phosphate as a non-solvated diluent can inhibit the main solvent and additives in the electrolyte from reacting with Li + , thereby increasing the affinity of Li + conduction efficiency and improve the fluidity of the electrolyte.

[0058] Among them, fluoroethylene carbonate as an additive can improve the electrolyte solubility and ion conductivity.

[0059] In the present application, the electrolyte is a mixture of LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB. The present application uses a variety of lithium salt electrolytes to increase the mixing entropy, and the high entropy electrolyte formed exhibits a richer and more diverse solvation structure, in which more salt anion groups interact with lithium ions. This highly disordered state weakens the interaction between lithium ions and salts and solvents, thereby forming a uniform liquid electrolyte.

[0060] In the present application, the total concentration of electrolyte in the electrolyte is 3 mol / L. Preferably, the concentrations of LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB in the electrolyte are equal, all of which are 0.5 mol / L. When the total solute concentration is less than 3.0 mol / L, that is, the concentration of each solvent is less than 0.5 mol / L, it is impossible to form a local high-concentration electrolyte, and it is difficult to achieve a more stable electrode / electrolyte interface and a higher lithium ion mobility. When the total solute concentration is greater than 3.0 mol / L, that is, the concentration of each solvent is greater than 0.5 mol / L, the viscosity of the electrolyte will increase, affecting the ion transmission speed and the charge and discharge performance of the battery. At the same time, the solubility of some electrolyte salts at high concentrations is limited, and high concentrations can cause the precipitation and precipitation of salts, affecting the stability of the electrolyte and the performance of the battery.

[0061] The chemical structure of the lithium salt electrolyte is shown below:

[0062]

[0063] In this application, the mixed electrolyte is dissolved in a composite solvent to prepare an electrolyte in an atmosphere of H2O < 0.01 ppm and O2 < 0.01 ppm. After the electrolyte is completely dissolved, a molecular sieve is added to the electrolyte and allowed to stand for 12 h to 15 h to further remove residual water and oxygen.

[0064] The present invention is based on a composite solvent and a mixed electrolyte to obtain a high entropy local high concentration electrolyte. It has excellent Li +It has excellent transmission kinetics and thermal stability, a wide electrochemical stability window and excellent flame retardancy, and can work stably under ultra-high voltage (4.7 V) and ultra-wide temperature (-50℃~70℃).

[0065] In the present application, the LiFBr is (3-fluoro-5-bromobenzenesulfonyl) (trifluoromethanesulfonyl) imide lithium, and its preparation method includes:

[0066] CF3SO2NHK and potassium carbonate are reacted at a molar ratio of (1.2-1.5):1 at room temperature for 36-40 hours, and then 3-fluoro-5-bromobenzenesulfonyl chloride is added dropwise to the reaction solution; the reaction solution is centrifuged to remove the solid phase, the filtrate is collected, and the filtrate is rotary evaporated to obtain a solid phase, and the solid phase is vacuum dried at 80-100°C for 10-12 hours to obtain KFBr;

[0067] In acetonitrile solvent, KFBr and LiClO4 are subjected to cation exchange at a molar ratio of (0.2-0.3):1 for 24-28 hours, and then the precipitate is removed by filtration, and the filtrate is evaporated to remove the solvent to obtain LiFBr.

[0068] In the present application, the preparation method of the 1,1′-oxybis(2-(2-fluoroethoxy)ethane) comprises:

[0069] S1, adding deoxyfluorine and 1,1′-oxybis(2-(2-hydroxyethoxy))ethane into dichloromethane for reaction, and then adding sodium bicarbonate solution to quench the reaction to obtain a crude product;

[0070] Specifically, deoxyfluorination and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) are added to a solvent at a temperature of 0°C to 25°C, and the reaction is stirred for 12h to 15h until the raw materials react completely, and then a sodium bicarbonate solution with a concentration of 1 mol / L is added to quench the reaction to obtain a crude product of 1,1′-oxybis(2-(2-hydroxyethoxy)ethane). The reaction formula is as follows:

[0071]

[0072] In the present application, in order to achieve better results, the molar ratio of deoxyfluorination to the 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) is preferably (2-2.2):1, and particularly preferably 2:1. When the molar ratio is greater than 2.2:1, the deoxyfluorination is excessive, resulting in excessive impurities after the reaction, requiring a longer time for impurity removal; when the molar ratio is less than 2:1, the reactants are insufficient and the reaction grafting is insufficient.

[0073] S2, the crude product is extracted with dichloromethane to remove impurities, dried, and then purified by flash chromatography to obtain 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

[0074] Specifically, the crude product of 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) was extracted with dichloromethane three times and then dried with anhydrous magnesium sulfate; after removing the desiccant by filtration, it was purified by flash chromatography.

[0075] In the present application, the preparation method of tris(trifluoromethyl) phosphate comprises:

[0076] S1. Under an inert atmosphere, trifluoromethanol and triethylamine are added to xylene and stirred evenly; phosphorus oxychloride is slowly added dropwise at a temperature of 0°C to 3°C to react to obtain a crude product solution; in the present application, the inert atmosphere is preferably a nitrogen atmosphere.

[0077] In the present application, the molar ratio of trifluoromethanol, triethylamine and phosphorus oxychloride is preferably 1: (0.5-0.6): (1-1.2); the molar ratio of trifluoromethanol to triethylamine is more preferably 1: 0.5, and the molar ratio of trifluoromethanol to phosphorus oxychloride is preferably 1: 1. Within this ratio range, the reaction is sufficient and the product contains few impurities.

[0078] Add trifluoromethanol and triethylamine to the xylene solution, stir for 5-10 minutes, keep the temperature at 0-3°C, slowly drop phosphorus oxychloride to react, the drop time is 3.5-5 hours, keep the temperature at 0°C for 2-4 hours, then stop the reaction to obtain a crude product solution. The reaction formula is as follows:

[0079]

[0080] S2, filtering the crude product solution and collecting the filtrate; washing the filtrate and then separating the layers and collecting the organic phase; drying the organic phase and concentrating it to obtain tris(trifluoromethyl) phosphate.

[0081] Specifically, the crude product was filtered to collect the filtrate, and the filtrate was washed with distilled water for 3 times, and then washed with sodium bicarbonate aqueous solution for 3 times. After separation, the organic phase was dried with anhydrous MgSO4, and then filtered to remove the MgSO4 drying agent, and the organic phase was concentrated at 35°C to 50°C for 1h to 2h to remove the solvent, and then heated to 50°C to 60°C and concentrated for 1h to 2h to further remove the solvent.

[0082] The high-voltage, wide-temperature-range electrolyte of the present application can be used to prepare a high-voltage, wide-temperature-range lithium battery. The high-voltage, wide-temperature-range electrolyte of the present application is a fluorinated high-entropy local high-concentration electrolyte, which helps to form inorganic-rich SEI and CEI layers, which have high conductivity, can achieve a more stable electrode / electrolyte interface, and higher lithium ion mobility, thereby greatly improving the performance of lithium batteries.

[0083] The present application also provides a lithium battery, which includes a positive electrode, a negative electrode, a separator and an electrolyte; the electrolyte is the high-voltage and wide-temperature electrolyte of the present application. The lithium battery using the electrolyte of the present application has excellent Li + It has excellent transmission kinetics and thermal stability, a wide electrochemical stability window and excellent flame retardancy, and can work stably under ultra-high voltage (4.7 V) and ultra-wide temperature (-50~70℃).

[0084] The present application is further described below by way of examples.

[0085] Example 1

[0086] This embodiment provides a method for preparing an electrolyte that is resistant to high voltage and has a wide temperature range, comprising:

[0087] Step 1, preparation of the main solvent 1,1′-oxybis(2-(2-fluoroethoxy)ethane):

[0088] At 25 °C, deoxyfluorine and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) were added to dichloromethane in a molar ratio of 2:1 for reaction and stirred for 12 hours until the reaction was complete. 1 mol / L sodium bicarbonate solution was added to the reaction solution to quench the reaction and obtain a crude product of 1,1′-oxybis(2-(2-fluoroethoxy)ethane). The crude product was extracted with dichloromethane three times, dried with anhydrous magnesium sulfate, filtered to remove the desiccant, and purified by flash chromatography to obtain 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

[0089] Step 2, preparation of diluent tris(trifluoromethyl) phosphate

[0090] At 0°C and under nitrogen protection, add 1 mol of trifluoromethanol and 0.5 mol of triethylamine to 50 mL of xylene, stir for 5 min, then slowly add 1 mol of phosphorus oxychloride to react at 1°C for 3.5 h; keep 0°C for 4 h and then stop the reaction. Filter the resulting reaction solution, wash the filtrate with distilled water 3 times, then wash it with sodium bicarbonate aqueous solution 3 times, separate the liquids, and take the organic phase and dry it with anhydrous MgSO4. Filter to remove the MgSO4 desiccant, concentrate the organic phase in an oven at 40°C for 1 h, then heat to 55°C and concentrate for 2 h to obtain tris(trifluoromethyl) phosphate.

[0091] Step 3, preparation of lithium (3-fluoro-5-bromobenzenesulfonyl)(trifluoromethanesulfonyl)imide (LiFBr)

[0092] CF3SO2NHK with a molar ratio of 1.2:1 was reacted with potassium carbonate (K2CO3), and then stirred at 25°C for 36 hours, after which 3-fluoro-5-bromobenzenesulfonyl chloride was added dropwise to the above suspension. After removing the insoluble solid, the filtrate was rotary evaporated to obtain a solid (KFBr), which was then dried at 80-100°C under vacuum for 12 hours.

[0093] In acetonitrile solvent, KFBr and LiClO4 with a molar ratio of 0.2:1 were subjected to cation exchange reaction for 24 h. After the exchange, the precipitate was filtered out and the excess solvent was rotary evaporated to obtain LiFBr.

[0094] Step 4: Prepare electrolyte

[0095] 1,1′-oxybis(2-(2-fluoroethoxy)ethane), tris(trifluoromethyl)phosphate and fluoroethylene carbonate (FEC) were mixed in a ratio of 2:2:1 to obtain a composite solvent;

[0096] Lithium (3-fluoro-5-bromobenzenesulfonyl) (trifluoromethanesulfonyl) imide (LiFBr), lithium hexafluorophosphate (LiPF6), lithium bis (trifluoromethanesulfonyl) imide (LiTFSI), lithium fluorosulfonyl imide (LiFSI), lithium difluorooxalatoborate (LiDFOB) and lithium dioxalatoborate (LiBOB) were added to 100 mL of composite solvent in sequence under an atmosphere of H2O < 0.01 ppm and O2 < 0.01 ppm, and mechanically stirred for 12-15 h to prepare an electrolyte with a total concentration of 3 mol / L and a concentration of 0.5 mol / L for all six solutes. After the electrolyte was uniform and transparent, molecular sieves were added to further remove water and oxygen. After standing for 12-15 h, an electrolyte with high voltage resistance and wide temperature range was obtained.

[0097] Example 2

[0098] Steps 1-3 of Example 2 are the same as those of Example 1.

[0099] In step 4 of Example 2, the molar ratio of 1,1′-oxybis(2-(2-fluoroethoxy)ethane), tris(trifluoromethyl)phosphate and fluoroethylene carbonate (FEC) was changed to 3:1:1, and the rest was the same as in Example 1.

[0100] Example 3

[0101] Steps 1-3 of Example 3 are the same as those of Example 1.

[0102] In step 4 of Example 3, the molar ratio of 1,1′-oxybis(2-(2-fluoroethoxy)ethane), tris(trifluoromethyl)phosphate and fluoroethylene carbonate (FEC) was changed to 1:3:1, and the rest was the same as in Example 1.

[0103] Example 4

[0104] Steps 1-3 of Example 4 are the same as those of Example 1.

[0105] In step 4 of Example 4, the molar ratio of 1,1′-oxybis(2-(2-fluoroethoxy)ethane), tris(trifluoromethyl) phosphate and fluoroethylene carbonate (FEC) was changed to 5:1:1, and the rest was the same as in Example 1.

[0106] Example 5

[0107] Steps 1-3 of Example 5 are the same as those of Example 1.

[0108] In step 4 of Example 5, the molar ratio of 1,1′-oxybis(2-(2-fluoroethoxy)ethane), tris(trifluoromethyl) phosphate and fluoroethylene carbonate (FEC) was changed to 1:5:1, and the rest was the same as in Example 1.

[0109] By proton nuclear magnetic resonance spectroscopy ( 1 H NMR) was used to characterize the chemical structure of the main solvent 1,1′-oxybis(2-(2-fluoroethoxy)ethane) prepared in Example 1. The results are as follows: Figure 1 shown. Figure 1 The chemical shifts corresponding to the 1,1′-oxybis(2-(2-fluoroethoxy)ethane) molecule are shown, proving the successful synthesis of the 1,1′-oxybis(2-(2-fluoroethoxy)ethane) molecule.

[0110] By proton nuclear magnetic resonance spectroscopy ( 13 C-NMR) was used to characterize the chemical structure of the diluent tris(trifluoromethyl) phosphate prepared in Example 1. The results are as follows Figure 2 shown. Figure 2 The chemical shift corresponding to the tris(trifluoromethyl)phosphate ester molecule is shown, proving the successful synthesis of the tris(trifluoromethyl)phosphate ester molecule.

[0111] The high-voltage, wide-temperature range electrolyte prepared in Example 1 was assembled into a Li||Cu button half-cell. First, the negative electrode shell was placed flat on an insulating table. The spring sheet and gasket were placed in turn with insulating tweezers. Then, the metal lithium sheet was placed and flattened. Then, the diaphragm was placed and the high-voltage, wide-temperature range lithium battery prepared in Example 1 was dripped. Finally, the copper foil was placed and the positive electrode shell was covered. Make sure that the active material side of the test electrode is close to the diaphragm. After the battery was assembled, the 1 mAh cm -2 @1 mA cm -2 The current density and deposition capacity of the copper foil were tested at different temperatures. The optical photos are shown in Figure 3 As shown. Figure 3It can be seen that at 70 °C, the lithium plating process can be carried out stably; at -50 °C, the copper foil can also be stably and comprehensively covered with lithium sheets, and a uniform silver-white lithium metal deposit visible to the naked eye is still produced. The rapid growth of bulk lithium forms an electron channel in the circuit, making it unnecessary to further Li in the electrochemical circuit. + Further observation of the scanning electron microscope (SEM) images of lithium deposition on the copper foil surface at different temperatures, such as Figure 4 As shown. Figure 4 It can be seen that seamless and uniform lithium blocks were observed at 70 °C, and dense lithium with a size of 10 μm was observed at 25 °C. Even when the temperature was reduced to -50 °C, the block size of lithium metal was reduced to 5 μm, but the electroplated lithium still showed a dense, dendrite-free deposition morphology. The above results are due to the fact that the introduction of a variety of lithium salts can increase the mixing entropy and increase the solubility of specific salts. The high-entropy liquid electrolyte formed has a diversified solvation structure, which weakens the interaction between lithium ions and salts and solvents, making the electrolyte more uniform.

[0112] The high-voltage, wide-temperature electrolyte prepared in Example 1 was paired with copper foil and lithium sheet to assemble a Li||Cu half-cell. The test results were as follows: -2 @1 mA cm -2 The electrochemical performance at different temperatures under current density is shown in the following test results: Figure 5 As shown. Figure 5 It can be seen that at 70 ℃, the battery can work stably, and the average coulombic efficiency is as high as 99.54% after 300 cycles; at the same time, at -50 ℃, the battery can still show stable cycling, and the average coulombic efficiency can still be maintained at 97.85% after 300 cycles, indicating that the electrolyte can work normally in a wide temperature range of -50 ℃ to 70 ℃.

[0113] The high-voltage, wide-temperature range electrolyte prepared in Example 1 is assembled into a Li||NCM811 button-type full battery. First, place the negative electrode shell flat on an insulating table, and use insulating tweezers to prevent the spring sheet and gasket in turn, then place the metal lithium sheet and flatten it. Then place the diaphragm and drip the high-voltage, wide-temperature range lithium battery prepared in Example 1, and finally place the purchased NCM811 positive electrode and cover it with the positive electrode shell (active material loading is 18.3 mg), ensuring that the active material side of the test electrode is close to the diaphragm. After the battery is installed, its performance is evaluated. Details are as follows:

[0114] 1. Test the electrochemical performance at different temperatures at a current density of 0.1 C and a voltage of 3-4.7 V. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that at 70 °C, the initial capacity is 218.8 mAh g-1 After 300 cycles, the battery has an ultra-high capacity retention rate of 99.58% and an average coulombic efficiency of 99.8%, and it can work stably. At -50 °C, the battery can also work stably, with a capacity of 172.6 mAh g -1 The initial capacity of the battery is 79.58% and the average coulombic efficiency is 98.65% after 300 cycles. This is because a variety of fluorinated lithium salts increase the mixing entropy, form inorganic-rich SEI and CEI layers on the anode and cathode surfaces, improve conductivity, stabilize the electrode / electrolyte interface, and increase lithium ion mobility, thereby increasing the voltage window of the lithium battery to 4.7 V.

[0115] 2. At a current density of 0.1 C and a voltage of 3~4.7 V, the charge and discharge curves of the 100th cycle at different temperatures were tested. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that at the 100th cycle, the electrochemical charge and discharge process of the Li||NCM811 full battery was stable without obvious fluctuations, and the charge and discharge voltage could be increased to 4.7 V; this shows that the high-entropy local high-concentration electrolyte exhibits excellent lithium ion transfer kinetics and thermal stability in an ultra-wide temperature range, has a wide electrochemical stability window and good flame retardancy, and can work stably in ultra-high voltage (4.7 V) and ultra-wide temperature range (-50~70 ℃).

[0116] 3. Test the electrochemical performance at different temperatures at different current densities. The test results are as follows: Figure 8 As shown. Figure 8 It can be seen that at room temperature, the average capacity of the Li||NCM811 full battery at 0.1 C is 221.7 mAh g -1 , it can still discharge stably at an ultra-high current density of 5 C, with an average capacity of 143.5 mAh g -1 When the temperature drops to -50 °C, the average capacity of the Li||NCM811 full cell at 0.1 °C is 210.3 mAh g -1 At an ultra-high current density of 5 C, the battery activity is still preserved, with an average capacity of 81.7 mAh g -1 When the temperature rises to 70 °C, the average capacity of the Li||NCM811 full cell at 1 C is 226.3 mAh g -1 At an ultra-high current density of 5 C, the battery did not spontaneously ignite, and its average capacity was 165.1 mAh g -1 The results show that the high-entropy local high-concentration electrolyte has good electrochemical performance in an ultra-wide temperature range of -50~70 ℃ and at different current densities.

[0117] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. An electrolyte resistant to high voltage and wide temperature range, characterized in that: including a complex solvent and an electrolyte; The electrolyte includes LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB, and LiBOB; the LiFBr is (3-fluoro-5-bromobenzenesulfonyl) (trifluoromethanesulfonyl) lithium imide; The composite solvent includes a main solvent having electron donor capability, a diluent for improving electrolyte fluidity, and an additive for increasing solute solubility and ion conductivity; Wherein, the main solvent is 1,1′-oxybis(2-(2-fluoroethoxy)ethane); The diluent is tris(trifluoromethyl) phosphate; The additive is fluoroethylene carbonate; In the electrolyte, the total concentration of electrolytes is 3 mol / L.

2. The high-voltage and wide-temperature electrolyte according to claim 1, characterized in that: The mass ratio of the main solvent, the diluent and the additive is (1-5):(1-5):

1.

3. The high-voltage and wide-temperature electrolyte according to claim 1, characterized in that: In the electrolyte, the concentrations of LiFBr, LiPF6, LiTFSI, LiFSI, LiDFOB and LiBOB are the same.

4. The high-voltage and wide-temperature range electrolyte according to claim 1, characterized in that: The preparation method of LiFBr comprises: CF3SO2NHK and potassium carbonate are reacted at room temperature in a molar ratio of (1.2-1.5):1, and then 3-fluoro-5-bromobenzenesulfonyl chloride is added dropwise to the reaction solution; after removing the solid phase from the reaction solution, the liquid phase is evaporated to obtain KFBr; In acetonitrile solvent, KFBr and LiClO4 are cation exchanged at a molar ratio of (0.2~0.3):1, and then the solid phase is removed and the liquid phase is evaporated to obtain LiFBr.

5. The high-voltage and wide-temperature-range electrolyte according to claim 1, characterized in that: The preparation method of the 1,1′-oxybis(2-(2-fluoroethoxy)ethane) comprises: Deoxyfluorine and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) are added to dichloromethane for reaction, and then sodium bicarbonate solution is added to quench the reaction to obtain a crude product; The crude product was extracted with dichloromethane to remove impurities, dried, and then purified by flash chromatography to obtain 1,1′-oxybis(2-(2-fluoroethoxy)ethane).

6. The high-voltage and wide-temperature range electrolyte according to claim 5, characterized in that: The molar ratio of deoxyfluorination and 1,1′-oxybis(2-(2-hydroxyethoxy)ethane) is (2-2.2):1; The reaction temperature is 0°C to 25°C; the reaction time is 12h to 15h.

7. The high-voltage and wide-temperature range electrolyte according to claim 1, characterized in that: The preparation method of the tris(trifluoromethyl) phosphate comprises: Under an inert atmosphere, trifluoromethanol and triethylamine are added to xylene and stirred evenly; phosphorus oxychloride is slowly added dropwise at a temperature of 0°C to 3°C to react to obtain a crude product solution; The crude product solution is filtered and the filtrate is collected; the filtrate is washed and separated, and the organic phase is collected; the organic phase is dried and concentrated to obtain tris(trifluoromethyl) phosphate; Wherein, the molar ratio of trifluoromethanol, triethylamine and phosphorus oxychloride is 1:(0.5-0.6):(1-1.2); The concentration is specifically as follows: the organic phase is kept at 35°C-50°C for 1h-2h, and then kept at 50°C-60°C for 1h-2h.

8. Use of the high-voltage-resistant and wide-temperature-range electrolyte according to any one of claims 1 to 7 in lithium batteries.

9. A lithium battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The electrolyte is the high-voltage and wide-temperature-range electrolyte as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Lithium secondary battery

    CN109690860A

  • High-cycle-stability lithium metal battery electrolyte suitable for multi-system positive electrode

    CN117996199A